2014
DOI: 10.1007/s00227-014-2470-2
|View full text |Cite
|
Sign up to set email alerts
|

New genetic markers to identify European resistant abalone to vibriosis revealed by high-resolution melting analysis, a sensitive and fast approach

Abstract: International audienceIncreasing temperature of seawater is often associated with increased exposure incidence of disease in field and in aquaculture populations. Numerous episodic mass mortalities of the abalone Haliotis tuberculata have been observed along the northern Brittany coast of France caused by a complex interaction between the host, pathogen and environmental factors. Here, we evaluated the potential of high-resolution melting (HRM) analysis for mutation genotyping and development of genetic marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Accordingly, detection of quantitative trait loci (QTL) and markers associated with resistance to bonamiosis could greatly accelerate the selection of breeders making the process much more efficient. Such resistance markers have been successfully found for some diseases in mollusks (He, Yu, Bao, Zhang, & Guo, 2012;Meistertzheim et al, 2014;Nie, Yue, & Liu, 2015;Nikapitiya et al, 2014;Normand et al, 2014;Raftos, Kuchel, Aladaile, & Butt, 2014;Schmitt, Santini, Vergnes, Degremont, & de Lorgeril, 2013), and particularly, several QTL for resistance to bonamiosis have been identified in flat oyster (Harrang et al, 2015;Lallias et al, 2009). These studies typically used low-medium density genetic maps and a small number of families and were able to identify some QTLs explaining up to 17% of the phenotypic variance in the trait (Harrang et al, 2015;Lallias et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, detection of quantitative trait loci (QTL) and markers associated with resistance to bonamiosis could greatly accelerate the selection of breeders making the process much more efficient. Such resistance markers have been successfully found for some diseases in mollusks (He, Yu, Bao, Zhang, & Guo, 2012;Meistertzheim et al, 2014;Nie, Yue, & Liu, 2015;Nikapitiya et al, 2014;Normand et al, 2014;Raftos, Kuchel, Aladaile, & Butt, 2014;Schmitt, Santini, Vergnes, Degremont, & de Lorgeril, 2013), and particularly, several QTL for resistance to bonamiosis have been identified in flat oyster (Harrang et al, 2015;Lallias et al, 2009). These studies typically used low-medium density genetic maps and a small number of families and were able to identify some QTLs explaining up to 17% of the phenotypic variance in the trait (Harrang et al, 2015;Lallias et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the molecular basis of the differences responsible for being susceptible or resistant to a particular disease and identifying molecular markers of resistance can help to fight against mollusc diseases. Recently, research effort has been focused on the identification of molecular markers of disease resistance, through transcriptomics (He et al, 2012; Meistertzheim et al, 2014; Nikapitiya et al, 2014; Nie et al, 2015; Wang et al, 2016; Gutierrez et al, 2018, 2020; La Peyre et al, 2019; De Lorgeril et al, 2020; Farhat et al, 2020; Proestou and Sullivan, 2020; Hasanuzzaman et al, 2020), proteomics (Simonian et al, 2009; Fernández-Boo et al, 2016; de la Ballina et al, 2018; Vaibhav et al, 2018; Smits et al, 2020; Leprêtre et al, 2021) and population genomics approaches (Vera et al, 2019; Sambade et al, 2022). This information could be eventually used for marker-assisted selection (MAS) programs to increase resilience against pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is caused by a range of Vibrio species, which can lead to mass mortality in a relatively short time (Jiang et al 2013). Vibriosis-associated mass mortalities in abalone have been reported in France (Travers et al 2008b, Pichon et al 2013, Cardinaud et al 2014a, Meistertzheim et al 2014, Australia (Handlinger et al 2005, Travers et al 2009b, Dang et al 2012, and Japan (Travers et al 2009b). Abalone vibriosis usually occurs when animals are immunosuppressed due to conditions such as elevated water temperature or spawning (Pichon et al 2013, Cardinaud et al 2014a.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that individual abalone undergoing gonad development are more susceptible to vibriosis, while immature abalone are more resistant to natural infection (Travers et al 2009a, Meistertzheim et al 2014. Since controlling water temperature on farms during such elevated temperatures is impractical for long periods of time, there is an industry need for effective vibriosis treatments for mature abalone.…”
Section: Introductionmentioning
confidence: 99%